Kompetensi Guru Dalam Pengelolaan Pembelajaran Kelas Di SD Negeri Tampar-Ampar Kecamatan Praya Tengah Kabupaten Lombok Tengah - Lale Novi Laela Purnama; Asrin Asrin; Ilham Syahrul Jiwandono (Universitas Negeri Makassar, 2021)
This study aims to determine how the competence of teachers in the management of SDN Tampar-ampar Praya. This research uses descriptive qualitative research methods. The research location is SDN Tampar-ampar Praya Tengah, Central Lombok Regency. Primary data sources are teachers and school principals, secondary data sources are the results of documentation. Data collection techniques using interviews and documentation. The data collected is in the form of words and pictures. Data analysis used Miles, Humberman, and Saldana models, namely data collection, data condensation, data presentation, and data verification. The results showed that the form of classroom management at SDN Tampar-ampar is (a) planning, compiling learning tools (b) implementing classroom management in supporting learning effectiveness, namely by motivating students to concentrate, conditioning students to be ready to learn in class, providing stimulus so that students are active in the classroom, using appropriate and varied methods, using media that is in accordance with the material presented (c) the constraints found in the classroom are that teachers still use monotonous learning methods.